2018
DOI: 10.21037/jtd.2018.09.30
|View full text |Cite
|
Sign up to set email alerts
|

Deep sternal infections after in situ bilateral internal thoracic artery grafting for left ventricular myocardial revascularization: predictors and influence on 20-year outcomes

Abstract: Link to publication on Research at Birmingham portal General rights Unless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law. • Users may freely distribute the URL that is used to identify this publication. • Users may download and/or print one copy of the publication from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…This method has been used for a long time; however, there is a 0.8–1.5% probability of sternal dehiscence or mediastinal infection after surgery [1]. The probability of sternal dehiscence or mediastinal infection could be as high as 2.4% after bilateral internal mammary artery grafting, thus leading to multiple complications and even death [2]. Shin reported that 34.5% of patients had poor sternal healing 3–6 months after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…This method has been used for a long time; however, there is a 0.8–1.5% probability of sternal dehiscence or mediastinal infection after surgery [1]. The probability of sternal dehiscence or mediastinal infection could be as high as 2.4% after bilateral internal mammary artery grafting, thus leading to multiple complications and even death [2]. Shin reported that 34.5% of patients had poor sternal healing 3–6 months after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The main limitation of our study was that the unilateral and bilateral ITA harvesting was not compared. Several studies have been performed to investigate the clinical safety of bilateral ITA harvesting and its effect on the risk of deep sternal infection [ 22 , 23 , 24 , 25 ]. However, we found no works, especially randomized, evaluating the effect of bilateral ITA harvesting on sternal perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery was carried out as previously reported [12,13]. Indication and contraindication for BITA was also the same as we have recently reported [13]: in summary patients with a reasonable life expectancy (>1year), those requiring minimization of aortic manipulation and the presence of at least two angiographically branches of the left coronary circulation which were graftable were included.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Surgery was carried out as previously reported [12,13]. Indication and contraindication for BITA was also the same as we have recently reported [13]: in summary patients with a reasonable life expectancy (>1year), those requiring minimization of aortic manipulation and the presence of at least two angiographically branches of the left coronary circulation which were graftable were included. Contraindications were: poorly controlled diabetes (defined as an uninterrupted HbA1c >8.0% for ≥1 year despite standard care [14], class III obesity, evolving or acute (6 hours to 7 days) myocardial infarction.…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation